Hydrophobic solubilizing method of oil shale semicoke and method for filling asphalt pavement by using oil shale semicoke
Through the hydrophobic and dissolving treatment of oil shale semi -burnt, a stable bonding structure is formed, and the problem of dissolving and creeping in the high humidity environment of oil shale is solved, and its water stability and water stability and water stability and Water resistance damage ability.
Patent Information
- Application Number
- CN202411457613.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-28
AI Technical Summary
Oil shale semicoke is prone to melt creep effects in high humidity environments or after contacting moisture, resulting in limited application in asphalt pavement and insufficient water stability and water damage resistance.
The surface treatment of the semi -focus of hydrophobic and dissolving hydraulic solution is used to prepare hydrophobic hydraulic solubility by shrinking glycelacelcelacer ether oxygen oxygen oxygenosilide with plasma water, and solidify the semi -focal surface of the oil shale shale Connecting to form a stable bonding structure to improve its water stability.
It significantly improves the semi -burnt water stability and water resistance damage ability, improves its compatibility with asphalt, prolongs the service life of asphalt mixture, and reduces the cost of material.
Smart Images

Figure CN119371132A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hydrophobic solubilization method of oil shale semi-coke and a method for filling asphalt pavement thereof, and belongs to the field of pavement materials. Background Art
[0002] As a strategic successor energy source, the efficient development and utilization of oil shale resources can reduce my country's dependence on foreign energy and improve my country's independent oil and gas supply capacity in the increasingly severe and complex international struggle situation. At present, the development and utilization of oil shale is mainly based on low-temperature distillation. Because oil shale contains a large amount of minerals, low-temperature distillation will produce a large amount of oil shale semi-coke, accounting for about 60% to 80% of the oil shale processing volume. Due to the incomplete recycling of oil shale semi-coke, a large amount of land needs to be occupied for open-air storage, which is easy to form dust and secondary water pollution, becoming the key to restricting the closed loop of the entire chain of the oil shale industry.
[0003] As a barren mineral material stripped from the original ore, oil shale semi-coke retains certain properties of the original ore, such as rich and developed pore structure, potential oil storage properties, and mineral aggregates with obvious particles. The main minerals contained in oil shale semi-coke are quartz, kaolinite, mica, hematite, corundum, dolomite, pyrite, etc. It is a barren mineral material similar to volcanic ash with a small amount of residual carbon. It has a certain particle size and good activity. It can replace part of the aggregate for the preparation of building materials. However, due to the hydrophilic surface of oil shale semi-coke, it is easy to experience melt creep effect in a high humidity environment or after contact with water, which has a negative impact on the mechanical properties.
[0004] In addition, the surface of oil shale semi-coke has a high content of SiO2, which makes the oil shale semi-coke acidic. The acidic aggregate has poor compatibility with asphalt. In a high humidity environment, water vapor can invade the contact interface between oil shale semi-coke and asphalt. The high temperature and high humidity cause the invading gas to expand, causing the contact interface between asphalt and aggregate to be destroyed, forming a weak layer on the aggregate surface, causing asphalt to peel off on the surface of oil shale semi-coke, limiting its application in the field of pavement materials.
[0005] Therefore, improving the water immersion sensitivity of oil shale semi-coke, improving its water stability performance for asphalt pavement, and forming a water damage prevention and control technology for oil shale semi-coke for asphalt pavement are the limiting bottlenecks that need to be broken through in this field. Summary of the invention
[0006] The present invention proposes a hydrophobic solubilization method of oil shale semi-coke and a method for filling asphalt pavement, which can play a key role in economy, development and ecological protection and has broad application prospects, can reduce the environmental pressure of the oil shale industry, ease the tension of land resources, reduce the demand for raw materials in the road industry, and expand the space for industrial economic development. If the promotion and application of oil shale semi-coke in national roads is realized, each cubic meter of asphalt mixture can consume about 0.3 to 0.5 tons of oil shale semi-coke, saving about 10% of direct material costs.
[0007] The present invention adopts the following technical solution:
[0008] A method for hydrophobic solubilization of oil shale semi-coke comprises the following steps:
[0009] S1. Glycidyl ether oxypropyl trimethoxysilane is mixed with plasma water to prepare a hydrophobic solubilizing hydrolyzate;
[0010] S2. Clean the dust, ash and dirt on the surface of the oil shale semi-coke and put it into an oven for drying;
[0011] S3. Spray the hydrophobic solubilizing hydrolyzate evenly on the surface of the oil shale semi-coke and place it in a high-temperature oven for solidification and association; obtain the hydrophobic solubilizing oil shale semi-coke.
[0012] The hydrophobic solubilization method of oil shale semi-coke of the present invention comprises the following steps: in step S1, glycidyloxypropyltrimethoxysilane is mixed with plasma water, ethanol is added, and the pH of the hydrolyzate is adjusted to 4-7; the hydrolysis time is 72 hours;
[0013] The mass fraction of the mixed solution of glycidyl ether oxypropyl trimethoxy silane and plasma water described in the present invention is 2%-10%.
[0014] In the hydrophobic solubilization method for oil shale semi-coke of the present invention, in step S2, dust, ash and dirt on the surface of the oil shale semi-coke are cleaned with ethanol deionized water and then placed in an oven at 60° C. and dried for 72 hours.
[0015] In the hydrophobic solubilization method for oil shale coke described in the present invention, in step S3, the mass of the hydrophobic solubilization hydrolyzate used is 2% of the mass of the oil shale coke, the temperature of solidification association is 150° C., and the time is 6 hours.
[0016] The hydrophobic solubilization method of oil shale semi-coke of the present invention is that the oil shale semi-coke is a porous industrial waste with high water absorption rate and containing active ingredients obtained by low-temperature dry distillation of oil shale, and has a high water absorption rate of 19%-26%. The water absorption rate of common stone is 0.1%-1%, which is much higher than the normal range of stone.
[0017] The asphalt pavement filling method of the hydrophobic solubilized oil shale semi-coke of the present invention comprises the following steps:
[0018] Step 1, determining the density, friction coefficient, normal stiffness and tangential stiffness of the hydrophobic solubilized oil shale semi-coke, and based on the microscopic parameters, constructing a discrete element calculation model to determine the filling particle size and material composition ratio of the oil shale semi-coke;
[0019] Step 2, premixing the hydrophobic solubilized oil shale semi-coke with stone to obtain a mixture of hydrophobic solubilized oil shale semi-coke and stone; wherein the content of the hydrophobic solubilized oil shale semi-coke aggregate is 2300-4600 parts; and the content of the stone is 5400-7000 parts;
[0020] Step 3, mixing the mixture prepared in step 1 with base asphalt to obtain a mixture containing base asphalt, wherein the base asphalt content is 522-681 parts;
[0021] Step 4: Mix the mixture prepared in step 2 with the mineral powder for a second time to obtain an asphalt mixture, wherein the mineral powder content is 450-1000 parts;
[0022] Step 5: After the asphalt mixture completed in step 4 is spread and compacted, it is cooled to room temperature to obtain the oil shale semi-coke hydrophobic solubilized asphalt pavement material.
[0023] In the asphalt pavement filling method of the hydrophobic solubilized oil shale semi-coke of the present invention, the stirring temperature in step 1 is 160° C. and the stirring time is 3 min; the stirring temperature in step 2 is 160° C. and the stirring time is 3 min; and the stirring temperature in step 4 is 160° C. and the stirring time is 3 min.
[0024] Beneficial Effects
[0025] As an acidic aggregate, oil shale semi-coke is used in asphalt pavement. Due to its surface particle characteristics and mineral composition, the water stability of asphalt mixture is reduced and water damage is serious, which restricts the large-scale application of oil shale semi-coke in asphalt pavement. The present invention creatively uses a hydrophobic solubilizing hydrolyzate to surface treat the oil shale semi-coke. At the same time, after cleaning and drying, the suspended particles on the surface of the oil shale can be removed to improve the compatibility with asphalt. The hydrophobic solubilizing hydrolyzate can solidify and associate on the surface of the oil shale semi-coke to form a stable bonding structure on its surface, which can effectively improve the water stability of the oil shale semi-coke as an aggregate and enhance the ability of the oil shale semi-coke as an aggregate to resist water damage in asphalt pavement. The present invention has a simple preparation process and strong operability, which promotes the large-scale application of oil shale in asphalt pavement.
[0026] 1. The present invention proposes a hydrophobic solubilization method for oil shale semi-coke, which can remove suspended particles on the surface of the oil shale after washing and drying, thereby improving compatibility with asphalt. The oil shale semi-coke is surface treated with a hydrophobic solubilizing hydrolyzate, which can solidify and associate on the surface of the oil shale semi-coke to obtain a hydrophobic solubilized oil shale semi-coke aggregate, thereby improving the poor compatibility of the oil shale semi-coke as an acidic aggregate with asphalt and improving the ability of the acidic aggregate to resist water damage.
[0027] 2. The present invention analyzes and discusses the stress mechanism of aggregates at various levels of asphalt pavement through PFC numerical simulation, obtains the main load-bearing particle size in asphalt pavement, separates the load-bearing particle size and the filling particle size. Oil shale semi-coke is determined as the filling particle size, and the optimal replacement range of oil shale semi-coke replacing asphalt mixture aggregate is obtained without reducing the road performance of asphalt pavement.
[0028] 3. The present invention uses oil shale semi-coke as raw material to prepare hydrophobic solubilized oil shale semi-coke aggregate, which is used to replace fine aggregate in asphalt pavement. The present invention has a simple preparation process and strong operability, and can expand the application scale of oil shale semi-coke to achieve the purpose of large-scale application of oil shale semi-coke. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Test results of residual stability index of hydrophobic solubilized oil shale semi-coke asphalt pavement soaked in water;
[0030] Figure 2 Test results of freeze-thaw residual stability index of hydrophobic solubilized oil shale semi-coke asphalt pavement;
[0031] Figure 3 The composition of oil shale semi-coke;
[0032] Figure 4 Numerical simulation model of AC-16 grading;
[0033] Figure 5 Contact angles of oil shale coke before and after solidification with hydrophobic solubilization hydrolysis liquid, where (a) is oil shale coke and (b) is hydrophobic solubilization oil shale coke. DETAILED DESCRIPTION
[0034] In order to make the purpose and technical solution of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] An AC-16 graded oil shale semi-coke hydrophobic solubilized asphalt pavement material is composed of 54 kg of granite stone, 5.83 kg of base asphalt, 6 kg of mineral powder, 46 kg of oil shale semi-coke, 0.046 kg of glycidyloxypropyltrimethoxysilane, and 0.414 kg of plasma water.
[0037] A hydrophobic solubilization method for oil shale semi-coke and a water damage prevention method for AC-16 graded asphalt pavement specifically comprises the following steps:
[0038] (1) 0.046 kg of glycidyloxypropyltrimethoxysilane was mixed with 0.414 kg of plasma water, and a small amount of ethanol was added to adjust the pH of the hydrolyzate to 4-7. The mixture was hydrolyzed for 72 hours to obtain a hydrophobic solubilization hydrolyzate.
[0039] (2) Weigh 46 kg of oil shale semi-coke, wash it with ethanol deionized water, and then put it into an oven at 60° C. to dry for 72 h.
[0040] (3) The hydrophobic solubilizing hydrolyzate is evenly sprayed on the surface of the oil shale semi-coke, and then placed in an oven at 150°C for curing and association for 6 hours.
[0041] (4) The prepared hydrophobic solubilized oil shale semi-coke was pre-mixed with 54 kg of granite material at a stirring temperature of 160° C. for 3 min.
[0042] (5) The mixture prepared above was mixed with 5.83 kg of base asphalt for initial mixing at a stirring temperature of 160° C. for 3 min.
[0043] (6) The mixture prepared above was mixed with 6 kg of mineral powder for a second mixing at a stirring temperature of 160° C. for 3 min.
[0044] (7) After the asphalt mixture is spread and compacted, it is cooled to room temperature to obtain an AC-16 graded oil shale semi-coke hydrophobic solubilized asphalt pavement material.
[0045] Embodiment 2
[0046] The invention discloses an OGFC-16 graded oil shale semi-coke hydrophobic solubilized asphalt pavement material, which is composed of 76.5 kg of granite stone, 5.22 kg of base asphalt, 4.5 kg of mineral powder, 23.5 kg of oil shale semi-coke, 0.092 kg of glycidyloxypropyltrimethoxysilane and 0.818 kg of plasma water.
[0047] A hydrophobic solubilization method for oil shale semi-coke and a water damage prevention method for OGFC-16 graded asphalt pavement specifically comprises the following steps:
[0048] (1) 0.092 kg of glycidyloxypropyltrimethoxysilane was mixed with 0.818 kg of plasma water, and a small amount of ethanol was added to adjust the pH of the hydrolyzate to 4-7. The mixture was hydrolyzed for 72 hours to obtain a hydrophobic solubilization hydrolyzate.
[0049] (2) Weigh 23.5 kg of oil shale semi-coke, wash it with ethanol deionized water, and dry it in an oven at 60° C. for 72 h.
[0050] (3) The hydrophobic solubilizing hydrolyzate is evenly sprayed on the surface of the oil shale semi-coke, and then placed in an oven at 150°C for curing and association for 6 hours.
[0051] (4) The prepared hydrophobic solubilized oil shale semi-coke was pre-mixed with 76.5 kg of granite material at a stirring temperature of 160° C. for 3 min.
[0052] (5) The mixture prepared above was mixed with 5.22 kg of base asphalt for initial mixing at a stirring temperature of 160° C. for 3 min.
[0053] (6) The mixture prepared above was mixed with 4.5 kg of mineral powder for a second mixing at a stirring temperature of 160° C. for 3 min.
[0054] (7) After the above-mentioned asphalt mixture is spread and compacted, it is cooled to room temperature to obtain the hydrophobic solubilized asphalt pavement material of OGFC-16 graded oil shale semi-coke.
[0055] Embodiment 3
[0056] A hydrophobic solubilization method of SMA-13 graded oil shale semi-coke asphalt pavement material, comprising 70 kg of granite stone, 6.81 kg of matrix asphalt, 10 kg of mineral powder, 30 kg of oil shale semi-coke, 0.138 kg of glycidyloxypropyl trimethoxysilane, 1.242 kg of plasma water, and 0.3 kg of basalt fiber. A hydrophobic solubilization method of oil shale semi-coke and a water damage prevention method for SMA-13 graded asphalt pavement specifically include the following steps:
[0057] (1) 0.138 kg of glycidyloxypropyltrimethoxysilane was mixed with 1.242 kg of plasma water, and a small amount of ethanol was added to adjust the pH of the hydrolyzate to 4-7. The mixture was hydrolyzed for 72 hours to obtain a hydrophobic solubilization hydrolyzate.
[0058] (2) Weigh 30 kg of oil shale semi-coke, wash it with ethanol deionized water, and dry it in an oven at 60° C. for 72 h.
[0059] (3) The hydrophobic solubilizing hydrolyzate is evenly sprayed on the surface of the oil shale semi-coke, and then placed in an oven at 150°C for curing and association for 6 hours.
[0060] (4) The prepared hydrophobic solubilized oil shale semi-coke was pre-mixed with 70 kg of granite material at a stirring temperature of 160° C. for 3 min.
[0061] (5) The mixture prepared above was mixed with 6.81 kg of base asphalt for initial mixing at a stirring temperature of 160° C. for 3 min.
[0062] (6) The mixture prepared above was mixed with 10 kg of mineral powder for a second mixing at a stirring temperature of 160° C. for 3 min.
[0063] (7) The mixture prepared above was mixed with 0.1 kg of basalt fiber three times at a stirring temperature of 160° C. for 3 min.
[0064] (8) After the asphalt mixture is spread and compacted, it is cooled to room temperature to obtain a hydrophobic solubilized asphalt pavement material of SMA-13 graded oil shale semi-coke.
[0065] Comparative Example 1
[0066] A conventional AC-16 graded asphalt pavement material is composed of 54 kg of granite stone, 46 kg of oil shale semi-coke, 5.83 kg of base asphalt, and 6 kg of mineral powder.
[0067] A conventional AC-16 asphalt pavement material specifically comprises the following steps:
[0068] (1) 54 kg of granite and 46 kg of oil shale semi-coke were pre-mixed at a stirring temperature of 160°C for 3 min.
[0069] (2) The mixture prepared above was mixed with 5.06 kg of base asphalt for initial mixing at a stirring temperature of 160° C. for 3 min.
[0070] (3) The mixture prepared above was mixed with 6 kg of mineral powder for a second mixing at a stirring temperature of 160° C. for 3 min.
[0071] (4) After the above asphalt mixture is spread and compacted, it is cooled to room temperature to obtain a conventional AC-16 graded asphalt pavement material.
[0072] Comparative Example 2
[0073] A conventional OGFC-16 graded asphalt pavement material is composed of 76.5 kg of granite stone, 23.5 kg of oil shale semi-coke, 4.88 kg of base asphalt, and 4.5 kg of mineral powder.
[0074] A conventional OGFC-16 graded asphalt pavement material specifically comprises the following steps:
[0075] (1) 76.5 kg of granite and 23.5 kg of oil shale coke were pre-mixed at a stirring temperature of 160 °C for 3 min.
[0076] (2) The mixture prepared above was mixed with 4.88 kg of base asphalt for initial mixing at a stirring temperature of 160° C. for 3 min.
[0077] (3) The mixture prepared above was mixed with 4.5 kg of mineral powder for a second mixing at a stirring temperature of 160° C. for 3 min.
[0078] (4) After the above asphalt mixture is spread and compacted, it is cooled to room temperature to obtain a conventional OGFC-16 graded asphalt pavement material.
[0079] Comparative Example 3
[0080] A conventional SMA-13 graded asphalt pavement material is composed of 70 kg of granite stone, 30 kg of oil shale semi-coke, 6.08 kg of base asphalt, 10 kg of mineral powder, and 0.3 kg of basalt fiber.
[0081] A conventional SMA-13 graded asphalt pavement material specifically comprises the following steps:
[0082] (1) 70 kg of granite and 30 kg of oil shale semi-coke were pre-mixed at a stirring temperature of 160°C for 3 min.
[0083] (2) The mixture prepared above was mixed with 6.08 kg of base asphalt for initial mixing at a stirring temperature of 160° C. for 3 min.
[0084] (3) The mixture prepared above was mixed with 10 kg of mineral powder for a second mixing at a stirring temperature of 160° C. for 3 min.
[0085] (4) The mixture prepared above was mixed with 0.1 kg of basalt fiber for three times at a stirring temperature of 160° C. and a stirring time of 3 min.
[0086] (5) After the above-mentioned asphalt mixture is spread and compacted, it is cooled to room temperature to obtain a conventional SMA-13 graded asphalt pavement material.
[0087] The results show that in Examples 1-3 and Comparative Examples 1-3, for the three gradation types of AC-16, SMA-13, and OGFC-16, the water-residual stability is increased by 5.59%-6.99% compared to the unsubstituted ones, and the freeze-thaw residual stability is increased by 6.96-14.14% compared to the unsubstituted ones. The water-residual stability and freeze-thaw residual stability far exceed the requirements of the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering". This preparation method can effectively improve the water stability of oil shale semi-coke for asphalt mixtures, indicating that the method of the present invention is feasible and effective. The hydrophobic solubilizing hydrolyzate changes the surface structure of the oil shale semi-coke, adds a coupling layer on the surface of the oil shale semi-coke, and enhances the interaction ability with asphalt on the acidic semi-coke surface. The hydrophobic solubilizing oil shale semi-coke has a better adsorption capacity for asphalt. The coupling structure connects asphalt and inorganic oil shale semi-coke, which can make the surface of the oil shale semi-coke coated with more asphalt, effectively reducing the excess asphalt content in the asphalt mixture and forming more structural asphalt. Improve the ability of asphalt mixture to resist water damage and change the stress characteristics of the entire structure.
[0088] In the above-mentioned Examples 1-3 and Comparative Examples 1-3, the oil shale semi-coke used was taken from the semi-coke slag field of a thermal power plant. The material has a thin layered joint structure of shale, and the main minerals contained are quartz, kaolinite, mica, hematite, corundum, dolomite, pyrite, etc. It is a barren mineral material similar to volcanic ash containing a small amount of residual carbon, has a certain particle size and grading characteristics, and has good activity. Its composition is as follows: Figure 3 shown.
[0089] The method for determining the filling particle size of oil shale semi-coke of the hydrophobic solubilized asphalt pavement material of oil shale semi-coke specifically comprises the following steps:
[0090] (1) Random partitioning is used to construct irregular particle shapes, and filling is performed based on the clump unit in PFC. The position and radius of the aggregate are overlapped and analyzed through the Ball module. The boundary constraints are set using the Wall module to establish a particle set with the target gradation. The density, friction coefficient, normal stiffness and tangential stiffness of the hydrophobic solubilized oil shale semi-coke are measured. Based on the microscopic parameters, a discrete element calculation model is constructed.
[0091] (2) Consider the types of contact models built into the discrete element and the construction characteristics of the model of the present invention as well as the mechanical properties between the various structures of the asphalt mixture.
[0092] The contact types between coarse aggregates in the target graded particle set are set to bonding model and viscoelastic model, the contact types between coarse aggregates are set to stiffness model and slip model, and the contact models of the internal units of fine aggregates are bonding model and viscoelastic model. The key parameters of the contact model are set according to the stress state of each structure inside the asphalt mixture and the actual engineering practice.
[0093] (3) Apply a downward load to the particle model at a cyclic speed of 1 / 1000 mm through the loading plate on the top of the particle assembly model in step 2, so that the spatial distribution of the particles changes and the internal model reaches equilibrium; the fine aggregate unit is displayed and hidden, and the changes in the force chain after the load is applied are observed.
[0094] (4) Call the system servo loading system to pressurize the particle system, obtain the contact force and point position of each particle in real time, and calculate the proportion P of the average contact force of each aggregate in the asphalt mixture gradation to the contact force of all aggregates in the entire gradation type. Under the action of vehicle load, the load will be transmitted through the contact points inside the asphalt mixture. At this time, by calculating the number of contact points and contact force of each aggregate, the contribution rate of the aggregate in a specific gear in resisting the load can be represented. The calculation formula is as follows:
[0095]
[0096] Where: F S It represents the average contact force of the aggregate in the Sth level in the asphalt mixture gradation, and n represents the total number of levels in the gradation type in the asphalt mixture.
[0097] The hydrophobic solubilizing hydrolyzate prepared in the above embodiment can form a hydrophobic film layer on the surface of the oil shale semi-coke through a dehydration condensation reaction between the hydroxyl groups in the alcohol molecules and the hydroxyl groups on the surface of the oil shale semi-coke, thereby changing the surface of the oil shale semi-coke from hydrophilic to hydrophobic. The contact angle test shows that the contact angle between the oil shale semi-coke and water is 34°, while the contact angle of the hydrophobic solubilizing oil shale semi-coke is 76.7°; the contact angle between the oil shale semi-coke and glycerol is 32.1°, while the contact angle of the hydrophobic solubilizing oil shale semi-coke is 66.2°. The hydrophobic solubilizing hydrolyzate can significantly improve the lipophilicity of the oil shale semi-coke.
[0098] The present invention improves the hydrophilicity of oil shale semi-coke, alleviates its melt creep effect in a high humidity environment or after contact with water, expands the application scenarios of oil shale semi-coke in asphalt pavements, reduces the material cost of asphalt pavement paving, has significant ecological and economic benefits, and is green, environmentally friendly, low-carbon, and high-value.
[0099] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for hydrophobic solubilization of oil shale semi-coke, characterized in that: The following steps are involved: S1. The glycidyl ether oxypropyl trimethoxysilane was mixed with plasma water to prepare a hydrophobic solubilizing hydrolyzate; S2. The dust, ash and dirt on the surface of the oil shale semi-coke are cleaned and placed in an oven for drying; S3. The hydrophobic solubilizing hydrolyzate is evenly sprayed on the surface of the oil shale semi-coke and placed in a high-temperature oven for solidification and association; and the hydrophobic solubilizing oil shale semi-coke is obtained.
2. The method for hydrophobic solubilization of oil shale semi-coke according to claim 1, characterized in that: In step S1, glycidyloxypropyltrimethoxysilane is mixed with plasma water, and then ethanol is added to adjust the pH of the hydrolyzate to 4-7; the hydrolysis time is 72 hours.
3. 2%-10% by mass of the mixed solution of glycidyloxypropyltrimethoxysilane and plasma water according to claim 1.
4. The method for hydrophobic solubilization of oil shale semi-coke according to claim 1, characterized in that: In step S2, the dust, ash and dirt on the surface of the oil shale semi-coke are cleaned with ethanol and deionized water, and then placed in an oven at 60° C. to dry for 72 hours.
5. The method for hydrophobic solubilization of oil shale semi-coke according to claim 1, characterized in that: In step S3, the mass of the hydrophobic solubilizing hydrolyzate used is 2% of the mass of the oil shale semi-coke, the temperature of solidification association is 150°C, and the time is 6 hours.
6. The method for hydrophobic solubilization of oil shale semi-coke according to claim 1, characterized in that: Oil shale semi-coke is a porous industrial waste with high water absorption rate and containing active ingredients obtained by low-temperature dry distillation of oil shale. It has a high water absorption rate of 19%-26%.
7. The asphalt pavement filling method of the hydrophobic solubilized oil shale semi-coke according to any one of claims 1 to 6, characterized in that: Here are the steps: Step 1, determining the density, friction coefficient, normal stiffness and tangential stiffness of the hydrophobic solubilized oil shale semi-coke, and based on the microscopic parameters, constructing a discrete element calculation model to determine the filling particle size and material composition ratio of the oil shale semi-coke; Step 2, premixing the hydrophobic solubilized oil shale semi-coke with stone to obtain a mixture of hydrophobic solubilized oil shale semi-coke and stone; wherein the content of the hydrophobic solubilized oil shale semi-coke aggregate is 2300-4600 parts; and the content of the stone is 5400-7000 parts; Step 3, mixing the mixture prepared in step 1 with base asphalt to obtain a mixture containing base asphalt, wherein the base asphalt content is 522-681 parts; Step 4: Mix the mixture prepared in step 2 with the mineral powder for a second time to obtain an asphalt mixture, wherein the mineral powder content is 450-1000 parts; Step 5: After the asphalt mixture completed in step 4 is spread and compacted, it is cooled to room temperature to obtain the oil shale semi-coke hydrophobic solubilized asphalt pavement material.
8. The asphalt pavement filling method of the hydrophobic solubilized oil shale semi-coke according to claim 7, characterized in that: In step 1, the stirring temperature is 160°C and the stirring time is 3 min; In step 2, the stirring temperature is 160°C and the stirring time is 3 min; In step 4, the stirring temperature is 160° C. and the stirring time is 3 min.